Angioleiomyoma of the Nasal Cavity - Arruda,Milena Moreira (2014)
Introduction Vascular leiomyoma of the nasal cavity is an extremely rare tumor that represents less than 1% of all vascular leiomyomas. It is more prevalent in women between the fourth and sixth decades, reaching primarily the inferior nasal turbinates. Objectives Reporting and assisting the systematization of more accurate diagnostic methods in clinical and complementary investigation of vascular leiomyoma in the nasal cavity. Resumed Report We present the case of a 49-year-old woman diagnosed with vascular leiomyoma in the nasal cavity, which manifested mainly with nasal obstruction. During investigation, computer tomography was not diagnostic, the cytologic study was not conclusive, and according to the biopsy, it was a squamous papilloma. Conclusion We suggest that the technical difficulty in obtaining an adequate amount of material for preoperative biopsy, associated with the topography of the lesion in the vestibular nasal region, may have contributed to changing the postoperative diagnosis. Thus, pathologic study of the surgical fragment is the more accurate method for diagnosis.